Clinical Characteristics of Short-Stature Patients With Collagen Gene Mutation and the Therapeutic Response to rhGH - Chen, Meiping; Miao, Hui; Liang, Hanting; Ke, Xiaoan; Yang, Hongbo; Gong, Fengying; Wang, Linjie; Duan, Lian; Chen, Shi; Pan, Hui; Zhu, Huijuan (Frontiers in Endocrinology, 2022)
Context: Clinical genetic evaluation has been demonstrated as an important tool to elucidate the causes of growth disorders. Genetic defects of collagen formation (the collagenopathies) have been reported to be associated with short stature with skeletal dysplasias. Etiological diagnosis of skeletal abnormalities-related short stature is challenging, and less is known about recombinant human growth hormone (rhGH) therapy. Objective: A single-center cohort study to explore the genetic architecture of short stature with skeletal abnormalities and evaluate the frequency of collagenopathies to determine their phenotype, including the treatment response. Patients and Methods: One hundred and six short stature patients with skeletal abnormalities by next generation sequencing (NGS) and searched for variants in the skeletal collagen genes including COL1A1, COL1A2, COL2A1, COL9A, COL9A2, COL9A3, COL10A1, COL11A1, and COL11A2 were enrolled. The results were evaluated using American College of Medical Genetics and Genomics (ACMG) guidelines. Clinical characteristics and rhGH treatment response were summarized. Results: Twenty-four pathogenic or likely pathogenic variants of collagen genes were found in 26 of 106 (24.5%) short stature patients with skeletal abnormalities, of which COL2A1 mutations were the most common, accounting for about 57.7%. Other frequent mutations associated with skeletal development include FGFR3, ACAN, NPR2, COMP, and FBN1 in 12.2%, 0.9%, 0.8%, 0.4%, and 0.4%, respectively, resulting in significantly different degrees of short stature. Overview of clinical features of collagenopathies showed growth retardation, skeletal abnormalities, and heterogeneous syndromic abnormalities involving facial, eye, hearing, and cardiac abnormalities. The average height of 9 patients who received rhGH treatment improved from a median of -3.2±0.9 SDS to -2.2±1.3SDS after 2.8±2.1 years. The most significant height improvement of 2.3 SDS and 1.7 SDS was also seen in two patients who had been treated for more than 6 years. Conclusions A proband-based NGS revealed distinct genetic architecture underlies short stature in varying degrees and clinical features. Skeletal abnormalities-related short stature involving multiple systems should be tested for skeletal collagen gene mutation. Limited rhGH treatment data indicate an improved growth rate and height, and close monitoring of adverse reactions such as scoliosis is required.